Genetic and phylogenetic uncoupling of structure and function in human transmodal cortex - Valk, Sofie L.; Xu, Ting; Paquola, Casey; Park, Bo-yong; Bethlehem, Richard A. I.; Vos de Wael, Reinder; Royer, Jessica; Masouleh, Shahrzad Kharabian; Bayrak, Şeyma; Kochunov, Peter; Yeo, B. T. Thomas; Margulies, Daniel; et al. (Nature communications, 2022)
Brain structure scaffolds intrinsic function, supporting cognition and ultimately behavioral flexibility. However, it remains unclear how a static, genetically controlled architecture supports flexible cognition and behavior. Here, we synthesize genetic, phylogenetic and cognitive analyses to understand how the macroscale organization of structure-function coupling across the cortex can inform its role in cognition. In humans, structure-function coupling was highest in regions of unimodal cortex and lowest in transmodal cortex, a pattern that was mirrored by a reduced alignment with heritable connectivity profiles. Structure-function uncoupling in macaques had a similar spatial distribution, but we observed an increased coupling between structure and function in association cortices relative to humans. Meta-analysis suggested regions with the least genetic control (low heritable correspondence and different across primates) are linked to social-cognition and autobiographical memory. Our findings suggest that genetic and evolutionary uncoupling of structure and function in different transmodal systems may support the emergence of complex forms of cognition. Brain structure scaffolds intrinsic function, supporting cognition and behavioral flexibility. Here, the authors show how macroscale organization of cortical microstructure and resting-state function uncouple in transmodal cortex of humans and macaques.